Investigating the Effects of Cuing Medication Availability on Patient-controlled Analgesia Pump Usage in Pediatric Patients: Results of a Randomized Controlled Trial. Issue 1 (January 2021) - Hainsworth, Keri R.; Czarnecki, Michelle L.; Simpson, Pippa M.; Zhang, Liyun; Davies, William H.; Mueller, Devin; Weisman, Steven J.
Abstract : Objectives: The study of patient-controlled analgesia (PCA) behaviors has led to a greater understanding of factors that affect the pain experience. Although PCA behaviors can be influenced by cues to medication availability, no studies have examined the effects of such cues in pediatric populations. Materials and Methods: This randomized controlled trial examined patient satisfaction with pain management, PCA behaviors, opioid consumption, and state anxiety in a sample of 125 postsurgical children and adolescents (7 to 17 y). Patients were randomized to a "light" group (lockout period status cued by light on the PCA button) or control group (no cues to medication availability). Results: Although cuing did not affect patient satisfaction with pain management ( P =0.11), patients in the light group consumed significantly more opioid than those in the control group (adj. P =0.016). This effect was primarily because of children in the light group (median, 0.019; interquartile range, 0.012 to 0.036 mg/kg/h) consuming more opioid than children (12 y or younger) in control group (median, 0.015; interquartile range, 0.006 to 0.025 mg/kg/h) ( P =0.007). In contrast to the control group, for patients in the light group, opioid consumption was unrelated to pain and the proportion of patients with a 1:1 injections:attempts ratio was higher ( P <0.001) across the study period. Discussion: The overall pattern of results suggests that patients in the light group used their PCA in response to the light more than in response to their pain, which likely reflects operant influences on PCA behavior by pediatric patients.